2015
DOI: 10.1016/j.mce.2014.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide inhibits osteoclast formation, bone resorption, RANKL-mediated NF-қB activation and titanium particle-induced osteolysis in a mouse model

Abstract: The RANKL-induced NF-κB signaling pathway is required for osteoclast formation and function. By screening for compounds that inhibit RANKL-induced NF-κB activation using a luciferase reporter gene assay in RAW264.7 cells, we identified triptolide (PG490), as a candidate compound targeting osteoclast differentiation and osteoclast-mediated osteolysis. Triptolide (PG490) is an active compound of the medicinal herb Tripterygium wilfordii Hook F (TWHF) or Lei Gong Teng with known anti-inflammatory properties. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 31 publications
(40 reference statements)
2
25
0
Order By: Relevance
“…Additional support for targeting RANK/RANKL arrives from studies demonstrating inhibition of osteolysis by: treatment with methotrexate, 95 ursolic acid, 96 and triptolide 97 (RANKL-mediated), p38 suppression 98 (downstream signaling cascade induced by RANKL), and RANK small interfering RNA local injection. 99 Methotrexate is an interesting option in that its effects are mainly mediated by the adenosine A 2A receptor, which has many downstream effects.…”
Section: Treatmentmentioning
confidence: 99%
“…Additional support for targeting RANK/RANKL arrives from studies demonstrating inhibition of osteolysis by: treatment with methotrexate, 95 ursolic acid, 96 and triptolide 97 (RANKL-mediated), p38 suppression 98 (downstream signaling cascade induced by RANKL), and RANK small interfering RNA local injection. 99 Methotrexate is an interesting option in that its effects are mainly mediated by the adenosine A 2A receptor, which has many downstream effects.…”
Section: Treatmentmentioning
confidence: 99%
“…In search for natural compounds that can inhibit osteolysis, we have conducted drug screening using combined osteoclastogenesis assays, and NF-κB and NFAT luciferase reporter gene assays. To this end, we have identified novel compounds that inhibit osteoclast formation and osteolysis [ 13 , 14 ]. In this study, we found that berberine sulfate, a derivative formula of unsulfated berberine that is easily absorbed, inhibits osteoclast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that triptolide has an effect on CD4 + and CD8 + cells in Peyer's patch and might be associated with immunosuppressive activities [ 26 ]. Triptolide plays a pivotal role in the inhibition of bone resorption by acting on osteoclasts and decreasing their resorption [ 27 ]. Wang et al also revealed that triptolide can enhance the levels of IL-10 in CIA rats and decrease the expression of T cell receptor variable gene mRNA [ 28 ].…”
Section: Discussionmentioning
confidence: 99%